2020
DOI: 10.18502/jad.v14i2.3732
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Characterization of Agglutinin Lectin from Heamolymph of German Cockroach, Blattella germanica

Abstract: Background: Lectin molecules have crucial biological role in insects’ immune system. The aim of present study was to find the agglutinin activities in haemolymph of German cockroach, Belatella germanica with appropriate screening and purification. Methods: The heamolymph of cockroach was collected and agglutinin test performed against different animal and human red blood cells (RBC). Then sugar inhibition assay was carried out to find carbohydrate specific binding lectin. The proteins of haemolymph was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Cockroaches have been noted to exhibit antimicrobial effects against both grampositive and gram-negative bacteria as well as antiamoebic effects, methicillin-susceptible Staphylococcus aureus (MSSA), M. luteus, and Bacillus subtilis. Another study revealed that cockroaches also have antimicrobial effects against Salmonella enterica, methicillin-resistant Staphylococcus aureus (MRSA), Streptococcus mutans, and Candida albicans in which all are recognised as drug resistant pathogens (Alkhalifah, 2021;Akbar et al, 2018;Basseri et al, 2016;Billah et al, 2015;Mahboub et al 2021), as shown in Figure 12. These investigations and their findings suggest that metabolites produced by gut bacteria in cockroaches could potentially be harnessed to create potent antibiotics or probiotics for use in treating or preventing drug-resistant pathogens.…”
Section: Antimicrobial Effects Of Edible Cockroachesmentioning
confidence: 99%
“…Cockroaches have been noted to exhibit antimicrobial effects against both grampositive and gram-negative bacteria as well as antiamoebic effects, methicillin-susceptible Staphylococcus aureus (MSSA), M. luteus, and Bacillus subtilis. Another study revealed that cockroaches also have antimicrobial effects against Salmonella enterica, methicillin-resistant Staphylococcus aureus (MRSA), Streptococcus mutans, and Candida albicans in which all are recognised as drug resistant pathogens (Alkhalifah, 2021;Akbar et al, 2018;Basseri et al, 2016;Billah et al, 2015;Mahboub et al 2021), as shown in Figure 12. These investigations and their findings suggest that metabolites produced by gut bacteria in cockroaches could potentially be harnessed to create potent antibiotics or probiotics for use in treating or preventing drug-resistant pathogens.…”
Section: Antimicrobial Effects Of Edible Cockroachesmentioning
confidence: 99%
“…Most cockroaches spend a large amount of time in sewers, drains, or sewer pipes that contain an abnormally high concentration of pathogens and sewage in which they live. This leads to high levels of disease and infection (Basseri et al, 2016). Also, they feed on garbage regularly, so they have access to large Coronavirus Disease Pandemic and Insects: A Historical Overview quantities of human pathogens given that they spend a lot of time eating garbage (Pai et al, 2003).…”
Section: Mechanical Transmissionmentioning
confidence: 99%